2016
DOI: 10.1177/0379572116659156
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Linkages Between Healthy Diets, Local Agriculture, and Sustainable Food Systems

Abstract: The School Meals Planner Package supported the design of nutritious, locally sourced menus for the school feeding program in Ghana. The tool can be similarly adapted for other countries to meet context-specific needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 12 publications
0
40
1
Order By: Relevance
“…This was contrary to the study observations in Eastern Cape and Mpumalanga, where posters on nutrition education were observed in school kitchens and classrooms [34]. Furthermore, the research findings are different from the study observations in Ghana School Feeding Programme, where nutrition education was partly achieved through the use of posters and songs promoting healthy diet [11].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was contrary to the study observations in Eastern Cape and Mpumalanga, where posters on nutrition education were observed in school kitchens and classrooms [34]. Furthermore, the research findings are different from the study observations in Ghana School Feeding Programme, where nutrition education was partly achieved through the use of posters and songs promoting healthy diet [11].…”
Section: Discussioncontrasting
confidence: 99%
“…One study in secondary schools in Nigeria observed that nutrition education songs had significant effect in improving adolescents' knowledge, attitude and practice of healthy eating [10]. Nutrition education in the Ghana School Feeding Programme was done using posters, songs promoting healthy diets and the meal planner tool enabled participants to learn about the nutrition value of locally available foods, and to determine the quantities of food stuffs to procure [11]. The Meal Planner Tool also enabled the planners to correctly estimate the quantity of food the caterer needs to prepare per child and maintains the quality of food.…”
Section: Introductionmentioning
confidence: 99%
“…Caterers are not allowed to serve >3 schools and their profits are made on margins after food procurement, preparation, and distribution. The school meal menus are designed at the district level to meet ∼30% of the recommended daily intake for children aged 6–12 y (21), and include foods grown by farmers in the community and the broader agroecological zone (22). School-level supervision on the quality of the service provision is provided by the School Implementing Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Menus were developed using a tool known as the School Meals Planner (Partnership for Child Development 2014; Fernandes et al 2016). The tool supports the design of menus that link dishes with the types and quantities (in grams) of each individual food.…”
Section: Methodsmentioning
confidence: 99%